Solidarity without the State? : Business and the Shaping of the Swiss Welfare State, 1890-2000. - Leimgruber, Matthieu (Cambridge University Press, 2008)
The first comprehensive, comparative study of the Swiss welfare system, based on extensive research in business archives.